2015
DOI: 10.2136/vzj2015.02.0028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two‐Dimensional and Three‐Dimensional Macroscopic Invasion Percolation Simulations with Laboratory Experiments of Gas Bubble Flow in Homogeneous Sands

Abstract: The upward flow of gas plays a role in many subsurface systems, including those related to oil and gas recovery, carbon dioxide storage, and groundwater remediation. Macroscopic invasion percolation (macro‐IP) is a modeling approach suitable for the simulation of upward gas flow, including bubble flow, in porous media, but few studies have compared simulations with experiments. Monte Carlo suites of macro‐IP simulations in two‐ and three‐dimensional domains were compared with small‐scale (∼10 cm) thin‐tank exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…The best-fit values of I r /I s for the 12/20, 20/30, and mixed sands were 0.69, 0.56, and 0.67, respectively. These values are consistent with the values of 0.71 ± 0.08 and 0.63 ± 0.07 for the 12/20 and 20/30 sands, respectively, reported previously using this technique (Mumford et al, 2015) to fit a ratio of transmitted light intensities for a dry and water-saturated pack. The error bars in Fig.…”
Section: Hydrogen Gas Productionsupporting
confidence: 91%
See 3 more Smart Citations
“…The best-fit values of I r /I s for the 12/20, 20/30, and mixed sands were 0.69, 0.56, and 0.67, respectively. These values are consistent with the values of 0.71 ± 0.08 and 0.63 ± 0.07 for the 12/20 and 20/30 sands, respectively, reported previously using this technique (Mumford et al, 2015) to fit a ratio of transmitted light intensities for a dry and water-saturated pack. The error bars in Fig.…”
Section: Hydrogen Gas Productionsupporting
confidence: 91%
“…Throughout the exsolution and relative permeability experiments, both following exsolution and following external drainage and imbibition, digital images were collected to quantify local gas saturations using a light transmission technique (Mumford et al, 2015; Niemet and Selker, 2001; Tidwell and Glass, 1994). The light transmission setup consisted of a light‐emitting diode (LED) panel (Led Go, CN‐1200H) behind the cell and a digital camera (Canon, EOS Rebel T3i) in front of the cell.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatial domain (illustrated in Figure ) was divided into 4‐×4‐×10‐mm grid blocks. While IP‐style models are fractal in nature, a previous MIP study has indicated that a resolution of 4 mm is sufficient to produce reasonable estimates of both local gas saturations and spatial moments with a MIP model (Mumford et al, ). Grid independence of the continuum portion of the model (i.e., the ‘ET’ model) was confirmed by comparing temperature distributions of model simulations with gas production disabled across a range of resolutions.…”
Section: Model Validation Proceduresmentioning
confidence: 99%